URGENSI FAKTOR INTERNAL KONSUMEN DALAM PENGAMBILAN KEPUTUSAN MENGGUNAKAN BIRO PERJALANAN UMRAH - Raden Yani (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2017)
The phenomenon of the increasing number of people who want to go Umrah even there are many times become an opportunity for Umrah travel agency, therefore many people are interested in this business field. This certainly makes the competition more competitive and to continue to exist Umrah travel agency must be able to provide satisfaction for its customers, so that one of the marketing studies of consumer decisions needs to be done, and the factors that become urgent to be reviewed is the internal factors of consumers in decision-making that is: culture, social class, individual characteristics, and psychological factors.